MANIFESTATION OF LATGALIAN IDENTITY IN EXILE - Malahovskis, Vladislavs (Via Latgalica, 2013)
The article deals with some aspects of Latgalian identity and perception in exile, their origin and main key issues. At the end of the Second World War about 120,000 - 140,000 residents of Latvia found their asylum in the West. About 7,000 of them were Latgalians. Despite their common sense of belonging to lost Latvia, common aspirations for freedom and independence of a Latvian state, Latvian intelligentsia was not united in exile. It was composed of different social and scientifi c organizations, etc. The lack of unity is based on heritage and stereotypes. Historically Latgale had different socio-economic conditions, different socio-political development of events and belated national consciousness development. That is why Latgalians in exile were not united. Their beliefs were very different in number of issues: 1. Regarding written language and the language of worship (Latvian or Latgalian). Catholic Church representatives in exile considered the language of worship services should be Latvian, because Catholics were among Latvians. But another part of the representatives of Latgalians insisted on the Latgalian language; 2. Regarding historical concept (authoritarian regime of Karlis Ulmanis and Latgale). One part criticized Karlis Ulmanis about restriction of the Latgalian language and literature in the second part of 30s of the 20th century, while the others supported his economic and other activities in favour of Latgale. The most active and important organization that defended everything Latgalian was Vladislavs Lōcis Publishing House and Latgale Research Institute (LRI). Vladislavs Lōcis Publishing House moved from Daugavpils to the West and started its activities in Germany. The publisher considered Latgalian writer or researcher a person who wrote in Latgalian. In this connection some problems arose with Latgalian authors who tried to keep both languages – Latgalian and Latvian. Despite of various ideological and material obstacles, V. Lōcis Publishing House has made a substantial contribution. The Publishing House issued in total about 150 Latgalian authors’ books, as well as almanac “Tāvu Zemes Kalendars” (Father`s Land Calendar), the newspaper “Latgolas Bolss” (Voice of Latgale), ”Latgola” (Latgale), the magazine ”Dzeive” (Life), a literary collection of articles “Olūts”, a scientific collection of articles “Acta Latgalica”. Research institute was established to coordinate research work in exile by the Latgale intelligentsia. Emphasising the authentic Latgalian research orientations, it is also known as Latgalian Research Institute. LRI foundation was a form of protest against disregard of the Latgalian descendants, history, culture, literary research: 1) In Western European research communities; 2) Works of Latvian group of authors in exile; 3) The absence of objective study of history of Latvia in Soviet Latvia. Though LRI staff were cut off from their homeland, without modern means of communication, nevertheless they were able to organize the Latgalian researchers in different countries and continents, could lead to permanent research in history, culture and literature of Latgale. The main issue as well as the problem was why during the second generation in exile has the continuity of selflessness ambitions vanished. During the first generation of exile the Latgalian identity has been largely reduced to the usage of Latgalian language. Unlike Latvians from other regions who saw spacious prospects for their activities, the new generation of Latgalians in exile did not see wide enough perspective for the Latgalian language and written form of expression of the language. However, the succession in greater or less extent was saved after the resumption of independence of Latvia – in Latgale: in 1991 the Institute activities were declared and supported by the official members of exile in Daugavpils. Currently, the LRI is the branch of Daugavpils University; Latgale research nowadays is not limited to LRI. Since 90s Rēzekne University College (Rēzeknes Augstskola) has grown into an important research centre, where the Institute of Regional Studies has started its activities. Latgale Cultural centre Publishing House continues traditions started by V. Lōcis.